Quality of basic emergency obstetric and newborn care (BEmONC) services from patients' perspective in Adigrat town, Eastern zone of Tigray, Ethiopia. 2017: a cross sectional study - Betell Berhane; Haftom Gebrehiwot; Solomon Weldemariam; Berhane Fisseha; Samson Kahsay; Alem Gebremariam (BMC, 2019)
Abstract Background Most of the maternal and newborn deaths occur at birth or within 24 h of birth. Provision of quality Basic Emergency Obstetric and Neonatal Care (BEmONC) is very crucial and the current recommended intervention to prevent maternal and newborn morbidity and mortality. Methods An institution based cross-sectional study was conducted among mothers receiving at least one of the signal functions of BEmONC services. A total of 398 women were included in the study. The study participants were selected using a systematic random sampling method. Data was collected using structured interviewer-administered Tigrigna version questionnaire. Data were analyzed using SPSS version 20. Multi-variable logistic regression was used to control the effect of confounders. Results The perceived quality of BEmONC was 66.7%, which is poor. Clients scored lower quality rates on aspects such as the availability of necessary equipment, lack of clean and functional shower and toilet and administration of anti-pain during delivery and manual vacuum aspiration (MVA). Quality of BEmONC was lower among rural residents (AOR = 0.273, 95% CI: (0.151-0.830). Whereas, Presence of companion (AOR = 2.259; 95% CI: (3.563-13.452) were found with a higher score of quality of BEmONC compared to their counterparts. Conclusion The overall perception of quality of BEmONC services received was poor. Residence, ANC follow-up, and presence of companion during labor or delivery were found to have a significant association with the perceived quality of BEmONC services.